Equity in park green spaces: a bibliometric analysis and systematic literature review from 2014-2023 - Yan, Lijie; Jin, Xiaoying; Zhang, Jinquan (Frontiers in Environmental Science, 2024)
With the global increase in population and the accelerated process of urbanization, the equitable access to park green spaces by diverse communities has become a growing concern. In order to provide an overview of the developmental trends, research focal points, and influencing factors in the study of equity in park green spaces, this paper employs bibliometric analysis and the visualization software CiteSpace to systematically analyze relevant literature in the Web of Science core database from 2014 to December 2023. The findings reveal an increasing emphasis on the research of equity in park green spaces, delineated into two distinct phases: a period of gradual exploration (2014-2018) followed by rapid development (2018 to present). Key nations contributing to research in this domain include China, the United States, and Germany. Currently, the research focus in this field primarily centers on the analysis of park green space equity based on primary social fairness, analysis of park green space equity based on vulnerable groups, and the relationship between park green spaces and health. The influencing factors of park green space equity mainly involve regional economic factors and government planning, as well as residents' economic capabilities and racial discrimination. Future research directions could include studying park green space equity among different demographic groups, emerging assessment methods and data, park green space equity based on perceived accessibility, and the relationship between park green space equity and surface temperature.